The efficacy of subcutaneous slow‐release melatonin implants in the prevention of canine flank alopecia recurrence is uncertain: A double‐blind, randomized, placebo‐controlled study. Issue 6 (15th September 2022) - Verschuuren, Millie U. M. Y.; Schlotter, Yvette M.; van Geijlswijk, Inge M.; van der Lugt, Jaco J.; Gehring, Ronette
Abstract: Background: Canine flank alopecia (CFA) is characterized by seasonally recurring noninflammatory, occasionally hyperpigmented alopecia predominantly in the thoracolumbar area. Previous studies suggest that reduced production of endogenous melatonin may play a role in the pathogenesis of this condition, and placebo‐controlled studies on the efficacy of preventative melatonin treatment are lacking. Objective: To evaluate the efficacy of subcutaneous slow‐release melatonin implants in the prevention of CFA recurrence. Animals: Twenty‐one client‐owned dogs with a history of CFA were included in the study. Materials and Methods: At time (T)0, a general physical and dermatological examination was performed on each dog, blood was collected for serum biochemistry analysis and two skin biopsies were taken from alopecic areas on the nonsedated affected dogs after subcutaneous injection with 2% lidocaine. Dogs with normal blood work and histological results compatible with CFA were included in the study. Participating dogs were randomly assigned to receive either placebo or 18 mg melatonin subcutaneously in the interscapular area, approximately 2 months before expected CFA onset (T1). CFA recurrence was scored qualitatively as complete, ≤50% recurrence, or no recurrence at 5 and 7 months after the intervention (T2 and T3, respectively). Results: At T3, in dogs treated with placebo (nine of 17), the percentages for complete recurrence, ≤50% recurrence and no recurrence were 44%, 0% and 56%, respectively. In dogs treated with melatonin (eight of 17), these percentages were 25%, 50% and 25%, respectively. There were no statistically significant differences in the scores between melatonin‐treated dogs and placebo‐treated dogs ( p  = 0.40). In three of eight melatonin‐treated dogs, mild transient swelling was observed at the injection site. Conclusions: This study did not provide evidence that an 18 mg melatonin implant treatment, although well‐tolerated, is efficacious in preventing recurrence of CFA in affected dogs. Abstract : Background – Canine flank alopecia (CFA) is characterized by seasonally recurring noninflammatory, occasionally hyperpigmented alopecia predominantly in the thoracolumbar area. Previous studies suggest that reduced production of endogenous melatonin may play a role in the pathogenesis of this condition, and placebo‐controlled studies on the efficacy of preventative melatonin treatment are lacking. Objective – To evaluate the efficacy of subcutaneous slow‐release melatonin implants in the prevention of CFA recurrence. Conclusions – This study did not provide evidence that an 18 mg melatonin implant treatment, although well‐tolerated, is efficacious in preventing recurrence of CFA in affected dogs. Résumé: Contexte: L'alopécie récidivante des flancs du chien (AFC) est caractérisée par une alopécie non inflammatoire récurrente de façon saisonnière, parfois hyperpigmentée, principalement dans la région thoraco‐lombaire. De précédentes études suggèrent qu'une production réduite de mélatonine endogène peut jouer un rôle dans la pathogénie de cette affection, et des études contrôlées par placebo sur l'efficacité du traitement préventif à la mélatonine font défaut. Objectif: Évaluer l'efficacité des implants sous‐cutanés de mélatonine à libération lente dans la prévention de la récidive de l'AFC. Animaux: Vingt et un chiens appartenant à des clients ayant des antécédents d'AFC ont été inclus dans l'étude. Matériels et méthodes: A T0, un examen physique et dermatologique général a été effectué sur chaque chien, du sang a été prélevé pour une analyse biochimique du sérum et deux biopsies cutanées ont été prélevées dans les zones alopéciques sur les chiens affectés non sédatifs après injection sous‐cutanée de 2 % lidocaïne. Des chiens avec un bilan sanguin normal et des résultats histologiques compatibles avec l'AFC ont été inclus dans l'étude. Les chiens participants ont été répartis au hasard pour recevoir soit un placebo, soit 18 mg de mélatonine par voie sous‐cutanée dans la zone interscapulaire, environ deux mois avant le début prévu de l'AFC (T1). La récidive de l'AFC a été notée qualitativement comme complète, ≤ 50 % de récidive ou aucune récidive à cinq et sept mois après l'intervention (T2 et T3, respectivement). Résultats: A T3, chez les chiens traités par placebo (neuf sur 17), les pourcentages de récidive complète, de récidive ≤ 50 % et d'absence de récidive étaient respectivement de 44 %, 0 % et 56 %. Chez les chiens traités à la mélatonine (huit sur 17), ces pourcentages étaient respectivement de 25 %, 50 % et 25 %. Il n'y avait pas de différences statistiquement significatives dans les scores entre les chiens traités à la mélatonine et les chiens traités au placebo ( p = 0, 40 ). Chez trois des huit chiens traités à la mélatonine, un léger gonflement transitoire a été observé au site d'injection. Conclusions: Cette étude n'a pas fourni de preuve qu'un traitement par implant de mélatonine à 18 mg, bien que bien toléré, soit efficace pour prévenir la récidive de l'AFC chez les chiens affectés. Resumen: Introducción: La alopecia canina de los flanco (CFA, por sus siglas en inglés) se caracteriza por una alopecia estacionalmente recurrente no inflamatoria, ocasionalmente hiperpigmentada, predominantemente en el área toracolumbar. Estudios previos sugieren que la producción reducida de melatonina endógena puede desempeñar un papel en la patogenia de esta afección, y faltan estudios controlados con placebo sobre la eficacia del tratamiento preventivo con melatonina. Objetivo: evaluar la eficacia de los implantes subcutáneos de melatonina de liberación lenta en la prevención de la recurrencia de la CFA. Animales: se incluyeron en el estudio veintiún perros de propietarios particulares con antecedentes de CFA. Materiales y Métodos: En el tiempo (T)0, se realizó un examen físico y dermatológico general a cada perro, se recolectó sangre para análisis de bioquímica sérica y se tomaron dos biopsias de piel de áreas alopécicas en los perros afectados no sedados después de la inyección subcutánea con 2% lidocaína. Se incluyeron en el estudio perros con análisis de sangre normales y resultados histológicos compatibles con CFA. Los perros participantes fueron asignados al azar para recibir placebo o 18 mg de melatonina por vía subcutánea en el área interescapular, aproximadamente dos meses antes del inicio esperado de la CFA (T1). La recurrencia de CFA se calificó cualitativamente como recurrencia completa, ≤50 % o sin recurrencia a los cinco y siete meses después de la intervención (T2 y T3, respectivamente). Resultados: En T3, en perros tratados con placebo (nueve de 17), los porcentajes de recurrencia completa, ≤50 % de recurrencia y sin recurrencia fueron 44 %, 0 % y 56 %, respectivamente. En perros tratados con melatonina (ocho de 17), estos porcentajes fueron del 25%, 50% y 25%, respectivamente. No hubo diferencias estadísticamente significativas en las puntuaciones entre los perros tratados con melatonina y los perros tratados con placebo ( p = 0, 40). En tres de los ocho perros tratados con melatonina, se observó una leve hinchazón transitoria en el lugar de la inyección. Conclusiones: este estudio no proporcionó evidencia de que un tratamiento con implantes de melatonina de 18 mg, aunque bien tolerado, sea eficaz para prevenir la recurrencia de la CFA en los perros afectados. Zusammenfassung: Hintergrund: Die Flankenalopezie des Hundes (CFA) ist durch eine saisonal wiederkehrende nicht entzündliche, gelegentlich hyperpigmentierte Alopezie charakterisiert, die hauptsächlich in der Thorakolumbalgegend auftritt. Frühere Studien haben gezeigt, dass eine reduzierte Produktion von endogenem Melatonin eine Rolle bei der Pathogenese dieser Veränderung spielen könnte; wobei Plazebo‐kontrollierte Studien über die Wirksamkeit präventativer Melatoninbehandlung fehlen. Ziel: Eine Evaluierung der Wirksamkeit von subkutanen Slow‐release Melatonin Implantaten bei der Verhinderung eines Wiederauftretens der CFA. Tiere: Einundzwanzig Hunde in Privatbesitz mit der Anamnese einer CFA wurden in die Studie aufgenommen. Materialien und Methoden: Zum Zeitpunkt (T) 0 wurde eine Allgemein‐ sowie eine dermatologische Untersuchung bei jedem Hund durchgeführt, es wurden Blut für eine Serumbiochemieanalyse und zwei Hautbiopsien von den haarlosen Stellen entnommen, nachdem den nicht sedierten Hunden mit Hautveränderungen eine subkutane Injektion von 2% Lidocain verabreicht worden war. Hunde mit normalen Blutuntersuchungsergebnissen und histologischen Befunden, die mit einer CFA vereinbar waren, wurden in die Studie aufgenommen. Teilnehmende Hunde wurden zufällig eingeteilt, um entweder Placebo oder 18 mg Melatonin subkutan in der interskapulären Gegend, ungefähr zwei Monate vor dem erwarteten Beginn der CFA (T1) subkutan verabreicht zu bekommen. Ein Wiederauftreten der CFA wurde qualitativ als vollständig, ≤50% Häufigkeit des Wiederauftretens, oder kein Wiederauftreten fünf bzw. sieben Monate nach der Behandlung (T2 bzw. T3) bewertet. Ergebnisse: Zum T3 lagen die Prozentwerte für ein totales Wiederauftreten, für ein ≤ 50% iges Wiederauftreten und kein Wiederauftreten bei den Hunden, die mit Plazebo behandelt worden waren (neun von 17), bei 44%, 0% bzw. 56%. Bei Hunden, die mit Melatonin behandelt worden waren (acht von 17), lagen diese Prozentsätze bei 25%, 50% bzw. 25%. Es bestanden keine statistisch signifikanten Unterschiede bei der Auswertung zwischen den Melatonin‐behandelten Hunden und jenen, die mit Plazebo behandelt worden waren ( p = 0, 40). Bei drei der acht mit Melatonin behandelten Hunde wurde eine milde vorübergehende Schwellung an der Injektionsstelle beobachtet. Schlussfolgerungen: Diese Studie erbrachte keine Evidenz, dass 18 mg Melatonin Implantate, obwohl sie gut toleriert wurden, das Wiederauftreten einer CFA bei betroffenen Hunden verhindern konnten. 要約: 背景: 犬の側腹部脱毛症(CFA)は、主に胸腰部に季節的に繰り返す非炎症性、時に色素沈着性の脱毛症が特徴である。これまでの研究で、内因性メラトニンの産生低下が本疾患の病因に関与している可能性が示唆されているが、メラトニンによる予防的治療の有効性に関するプラセボ対照試験は行われていない。 目的: 本研究の目的は、 CFA の再発予防におけるメラトニン徐放性皮下インプラントの有効性を評価することであった。 対象動物: CFA の既往のあるオーナー所有犬 21 頭を本研究に組み入れた。 材料と方法: 研究初日(T0)に、各犬に対して一般的な身体検査と皮膚科学的検査を行い、血清生化学分析のために採血し、2%リドカインを皮下注射した後、非沈静下の患犬脱毛部から2ヶ所の皮膚生検を行った。血液検査が正常で、組織学的な結果がCFAに適合する犬が研究に参加した。参加した犬は、CFA発症予定日の約2か月前に、プラセボまたは18mgのメラトニンを肩甲骨間部に皮下投与する群に無作為に振り分けられた(T1)。CFAの再発は、介入後5ヶ月および7ヶ月(それぞれT2およびT3)において、完全、50%以下の再発、または再発なしとして定性的にスコア化された。 結果: T3において、プラセボ投与犬(17頭中9頭)では、完全再発、50%以下の再発、無再発の割合は、それぞれ44%、0%、56%であった。メラトニン治療犬(17頭中8頭)では、これらの割合はそれぞれ25%、50%、25%であった。メラトニンを投与した犬とプラセボを投与した犬の間には、スコアに統計的に有意な差はなかった(p = 0.40)。メラトニン投与犬8頭中3頭で、注射部位に軽度の一過性の腫脹が観察された。 結論: 本研究は、18mgのメラトニンインプラント治療が、患犬のCFA再発防止に有効であることを示す証拠とはならなかった。 摘要: 背景: 犬侧腹脱毛症 (CFA) 的特征为季节性复发的非炎性、偶见色素沉着的脱毛症，主要发生在胸腰区。以往的研究认为，内源性褪黑素的产生减少可能在这种情况的发病机制中起作用，缺乏预防性褪黑素治疗疗效的安慰剂对照研究。 目的: 评价皮下缓释褪黑素植入剂预防 CFA 复发的疗效。 动物: 本研究纳入了21只具有 CFA 病史的私家犬。 材料和方法: 在时间 (T)0 时，对每只犬进行全身体格检查和皮肤病学检查，采集血液进行血清生化分析，并在局部皮下注射2%利多卡因后，从未镇静患犬的脱毛区域采集两份皮肤活检组织。血液检查正常且组织学结果符合 CFA 的犬，被纳入研究。参与研究的犬被随机分配在预期 CFA 发作前约2个月 (T1) 在肩胛间区皮下接受安慰剂或 18 mg 褪黑素。CFA 复发定性评分为完全复发、≤50%复发或干预后5个月和7个月无复发(分别为 T2 和T3)。 结果: 在 T3 时，在接受安慰剂治疗的犬中(17只中的9只)，完全复发、≤50%复发和无复发的百分比分别为44%、0%和56%。在接受褪黑素治疗的犬中 (8/17)，这些百分比分别为25%、50%和25%。褪黑激素治疗犬和安慰剂治疗犬之间的评分无统计学显著差异 (p = 0.40)。在3/8只褪黑激素处理的犬中，在注射部位观察到一过性轻度肿胀。 结论: 本研究未能证明 18 mg 褪黑素植入有效，尽管耐受性良好。 Resumo: Contexto: A alopecia sazonal do flanco (ASF) é uma doença caracterizada por alopecia sazonal recorrente, não inflamatória e ocasionalmente hiperpigmentada que ocorre predominantemente na região toracolombar. Estudos anteriores sugerem que uma redução na produção de melatonina pode participar na patogênese desta condição, e são escassos os estudos placebo‐controle sobre a eficácia do tratamento preventivo com melatonina. Objetivo: Avaliar a eficácia de implantes de melatonina de liberação lenta na prevenção da recorrência de ASF. Animais: Vinte e um cães de clientes com histórico de ASF foram incluídos no estudo. Materiais e métodos: No tempo (T)0, realizou‐se uma avaliação física geral e dermatológica de cada animal, coletou‐se sangue para análise bioquímica sérica e duas biópsias cutâneas foram coletadas das áreas alopécicas nos cães afetados, sem sedação, após injeção subcutânea de lidocaína 2%. Cães com exames de sangue normais e resultados histológicos compatíveis com ASF foram inclusos no estudo. Os cães participantes foram divididos aleatoriamente para receber placebo ou 18mg de melatonina, por via subcutânea, na região interescapular, aproximadamente dois meses antes do ínicio esperado do quadro de ASF (T1). A recorrência de ASF foi classificada qualitativamente como completa, ≤50% de recorrência, ou nenhuma recorrência em cinco e sete meses após a intervenção (T2 e T3, respectivamente). Resultados: No T3, os cães tratados com placebo (nove de 17), as porcentagens de recorrência completa, ≤50% de recorrência e nenhuma recorrência foram 44%, 0% e 56%, respectivamente. Não houve diferenças estatísticas nos escores entre cães tratados com melatonina e cães tratados com placebo ( p = 0.40). Em três de oito cães tratados, observou‐se um aumento de volume discreto transitório no local da injeção. Conclusões: Este estudo não demonstrou evidências de que o tratamento com melatonina, apesar de bem tolerado, é eficaz na prevenção da recorrência de ASF em cães afetados.